Perception of Patient with Hypertension about Complementary - Mohammad Abu Serrieh; Kareem Attili Hos; ney Ismael; Omar Shehadah (My University, 2015)
Introduction: hypertension is a common health problem with a prevalence rate of 45.3% among Palestinian in 2012. The Management therapy still considered the only the pharmacological use while it should based on patients individual cases and their experiences. This studyaimedto find out the perception and uses about different complementary /herbal therapy for hypertension. Design:mixed approach; quantitative and qualitative approach using cross – sectional method for quantitative design and phenomenological one for qualitative design. One hundred and twenty hypertensive participants have been involved in the study by convenience sampling method from the primary health care (Al-Makhfia, Al- Wosta) in Nablus. Face to face interview was used to fulfill the questionnaire. Eight hypertensive participant were interviewed to answer semi-structure question for qualitative. Result:of the 120 hypertensive participants interviewed, 56.7% used herbal therapy for hypertension with 51.5% age range between56-60 years. Garlic was the most common herbal type used for hypertension as 39.7% reported using it. The most common source of information for used herbal was the relative and family with 60.3% .About 76.5% of participants who used herbal were using it without informed their doctor. Conclusion:herbal therapy among hypertensive patient is widely common in Nablus city without medical intervention or advices.Recommendations:health care center should do a program to educate the hypertensive patients about the using of herbal therapy, their side effect and the method of preparing it.
Keywords: hypertension, herbal, complementary therapy, alternative therapy.